If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 2) = 38 Reorder the terms: 6(2 + x) = 38 (2 * 6 + x * 6) = 38 (12 + 6x) = 38 Solving 12 + 6x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 38 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 38 + -12 6x = 38 + -12 Combine like terms: 38 + -12 = 26 6x = 26 Divide each side by '6'. x = 4.333333333 Simplifying x = 4.333333333
| 6x+1=10-3x | | 6x+10y=6302 | | 2x=6x-15 | | 5m+8+4(3m-3)-3(m+3)=0 | | ln(2x+3)=2 | | -(6x-5)-(4x-5)+13=-11(x-1)-(4x+11)+3 | | 1.5y+2x=20 | | 4+9x+x=20x-35 | | -85-9x=104-30x | | 3(a-4)=7z+4 | | 4m+8+5(4m-5)-5(m+5)=0 | | x^2-(2a-1)x+a^2-a+1=0 | | 0.57x^3+4x=4 | | 70x+90y=350 | | 0.2(p+6)-0.7(p+4)=-3 | | 0.57x^3+4u=4 | | 6y+12-4=-10 | | 4b^2+b-19=0 | | 3x+4(2x-3)=6 | | 2(f-9)=-24 | | 4=x^4 | | 3+2y-24=14 | | 7+3x=7x-29 | | 45=x-36 | | 6c-1=23 | | 216=5x | | -3(2t+3)=-3 | | -133=-7(6n+7) | | -2x+3(3x-6)=-2-9x | | 10(s-4)=-85 | | 2m-8=10+18 | | 3x+1y=392 |